How corruption hits people when they are down - Jennifer Hunt (Institute for the Study of Labor (IZA), 2006)
Using cross-country and Peruvian data, I show that victims of misfortune, particularly crime victims, are much more likely than non-victims to bribe public officials. Misfortune increases victims' demand for public services, raising bribery indirectly, and also increases victims' propensity to bribe certain officials conditional on using them, possibly because victims are desperate, vulnerable, or demanding services particularly prone to corruption. The effect is strongest for bribery of the police, where the increase in bribery comes principally through increased use of the police. For the judiciary the effect is also strong, and for some misfortunes is composed equally of an increase in use and an increase in bribery conditional on use. The expense and disutility of bribing thus compound the misery brought by misfortune
Keywords: 330; Kriminalität; Kündigung; Krankheit; Soziales Problem; Korruption; Welt; Peru